Proposed Implementation Of Activity-Based Costing To Determine Cost Allocation In Manufacturing Company PT. S - Indy Larasati; Nureni Wijayati (UNIVED Press, 2024)
This research discusses the proposal for implementing Activity-Based Costing (ABC) in the cardboard box manufacturing company, PT. S, focusing on Plant 4 located in West Java. The products produced include standard A1 cardboard boxes, A1 printing, plain die-cut boxes, printed die-cut boxes, and top-bottom boxes. The application of the ABC approach is carried out with the intention of presenting more detailed cost information through the identification and allocation of costs to the various activities involved in the production process. The traditional method appears to be inappropriate as overhead allocation only burdens direct raw material costs, direct labor costs, shipping costs, and sales commission to products using percentages from historical data as a reference for the selling price of the product. The research type is problem-solving with a descriptive qualitative research method. The results indicate that the ABC method provides more accurate calculations by allocating costs per activity that are then assigned to products. Among the five studied products, it is found that the plain A1 product is the least profitable. On average, the allocation of product costs experiences undercosting, except for plain die-cut products that experience overcosting. PT. S needs to consider the use of the ABC method in product cost and product selling prices to be able to reduce costs and increase the profitability